Heart rate turbulence assessed through ergometry after myocardial infarction: a feasibility study - Rafael Alessandro Ferreira Gomes; Dário Celestino Sobral-Filho (São Paulo Medical Journal, 2022)
ABSTRACT BACKGROUND: Coronary artery disease is an important cause of morbidity and mortality. The impact of ventricular arrhythmias with impaired cardiac vagal activity is one of the most recently studied prognostic factors. However, there are no studies evaluating the phenomenon of heart rate turbulence (HRT) during physical exertion. OBJECTIVE: To study the behavior of HRT during exercise testing, among individuals after myocardial infarction. DESIGN AND SETTING: Feasibility study conducted in a university hospital among individuals 4-6 weeks after myocardial infarction. METHODS: All subjects underwent 24-hour Holter monitoring and ergometric stress testing. We considered that abnormal HRT was present if the turbulence onset was ≥ 0% or turbulence slope was ≤ 2.5 mm/relative risk interval. RESULTS: All 32 subjects were asymptomatic. Their median age was 58 years (interquartile range 12.8) and 70% were male. Abnormal HRT was associated with ventricular dysfunction in this population. We found no differences regarding the behavior of HRT, in relation to age, gender, smoking, systemic arterial hypertension, diabetes mellitus or dyslipidemia. Ergometric stress testing detected premature ventricular beats (PVB) in approximately 44% of the examinations, and these occurred both during the active phase of effort and in the recovery period. The low occurrence of several isolated PVB in beta-blocked subjects made it difficult to perform statistical analysis to correlate HRT between ergometric and Holter testing. CONCLUSION: The data obtained in this study do not support performing HRT through ergometric stress testing among patients who remain on beta-blockers post-myocardial infarction, for the purpose of assessing cardiac vagal activity.